Extramedullary Hematopoiesis in the Dura Mater During Treatment of a CNS Embryonal Tumor. Issue 8 (November 2021) - Ganapathi, Shireen S.; Havard, Molly E.; Ferguson, Mark; Cole, Bonnie L.; Millard, Nathan E.; Vitanza, Nicholas A.
Abstract : Extramedullary hematopoiesis (EMH) is hematopoiesis occurring outside of the bone marrow. It has been reported to develop in abdominal organs or lymph nodes after chemotherapy. Here, the authors describe a patient with a localized central nervous system embryonal tumor who, during intensive chemotherapy, developed dural nodules. Biopsy revealed these nodules to be EMH. Without a pathologic diagnosis, this may have been considered disease progression, altering the patient's treatment plan. This report intends to serve as a reminder that EMH should be included in the differential diagnosis of suspicious lesions and highlights the importance of their biopsy because of potential management implications.